Parapharyngeal abscess: A difficult diagnosis in younger children. Issue 6 (10th May 2019) - Sudhanthar, Sathyanarayan; Garg, Anjali; Gold, Jonathan; Napolova, Olga
Abstract: Parapharyngeal abscess is a difficult diagnosis to make in the pediatric population. Children <3 years of age present with fever, often the only sign at the initial presentation, thus causing a delay in diagnosis until the patient presents with more focal findings, such as a painful neck mass. Repeated follow‐up visits with the patient until the diagnosis is confirmed are critically important to prevent complications. Abstract : Parapharyngeal abscess is a difficult diagnosis to make in the pediatric population. Children <3 years of age present with fever, often the only sign at the initial presentation, thus causing a delay in diagnosis until the patient presents with more focal findings, such as a painful neck mass. Repeated follow‐up visits with the patient until the diagnosis is confirmed are critically important to prevent complications.